Наномодифіковані надшвидкотверднучі цементуючі системи та високофункціональні бетони на їх основі - Марущак, Уляна Дмитрівна (Національний університет "Львівська політехніка", 2019)
Дисертаційна робота присвячена розробленню теоретичних основ одержання наномодифікованих надшвидкотверднучих цементуючих систем для ефективних високофункціональних бетонів на їх основі з покращеними будівельно-технічними властивостями в умовах різних експлуатаційних впливів. Визначено принципи наномодифікування високорухливих цементних матриць для синтезу підвищеної міцності в ранній період тверднення за рахунок використання комплексних органо-мінеральних наномодифікаторів на основі ультрадисперсних мінеральних компонентів, а також полікарбоксилатних суперпластифікаторів з наноспроектованими ланцюгами. Встановлено фізико-хімічні закономірності процесів гідратації та тверднення наномодифікованих цементуючих систем, що полягають у направленому формуванні мікроструктури цементуючої матриці з прискореним формуванням гідросилікатного гелю, рівномірним розподіленнням гідратів в обмеженому міжзерновому просторі та утворенням однорідної дрібнокристалічної структури цементного каменю. У дисертації розроблено системний підхід до композиційної побудови ефективних високофункціональних бетонів, що полягає у полімасштабному модифікуванні та армуванні структури композиту на нано-, мікро- та мезорівнях для одержання необхідних технологічних, міцнісних та експлуатаційних властивостей. Здійснено промислове впровадження та визначено техніко-економічну ефективність використання наномодифікованих надшвидкотверднучих цементуючих систем та високофункціональних бетонів на їх основі. Диссертация посвящена разработке теоретических основ получения наномодифицированных сверхбыстротвердеющих цементирующих систем для эффективных высокофункциональных бетонов на их основе с улучшенными строительно-техническими свойствами в условиях различных эксплуатационных воздействий. Установлены принципы наномодифицирования высокоподвижных цементных матриц для синтеза повышенной прочности в ранний период твердения за счет использования комплексных органо-минеральных наномодификаторов на основе ультрадисперсных минеральных компонентов, а также поликарбоксилатных суперпластификаторов с наноспроектированными цепями. Изучены физико-химические особенности процессов гидратации и твердения наномодифицированных цементирующих систем, которые определяют направленное формирование микроструктуры цементирующей матрицы с ускоренным образованием гидросиликатного геля при более однородном распределении гидратов в ограниченном межзерновом пространстве и образованием однородной мелкокристаллической структуры цементного камня. В диссертации разработан системный подход к композиционному построению эффективных высокофункциональных бетонов многоуровневой структуры, состоящий в полимасштабном модифицировании и армировании структуры композита для достижения необходимых технологических, прочностных и эксплуатационных свойств. Осуществлена промышленная апробация и рассчитана технико-экономическая эффективность использования наномодифицированных сверхбыстротвердеющих цементирующих систем и высокофункциональных бетонов на их основе. The thesis is devoted to the development of theoretical bases of obtaining nanomodified ultrarapid hardening cementitious systems for efficient high performance concrete on their basis with improved building and technical properties in different exposure conditions. The principles of nanomodification of high flowability cement matrix for the synthesis of high strength in the early hardening period due to the system combination of nano- and ultrafine mineral components and superplasticizer based on the polycarboxylate ether with nano-engineered chains have been established. The scientific understanding of the formation of the hierarchical structure of cement systems on the micro- and nanolevels on the basis of the multiparametric analysis of the granulometric distribution of ultrafine components, taking into account the relationship between the elements of the matrix and pore space is expanded. The physical and chemical peculiarities of the processes of hydration and hardening of nanomodified cementitious systems, which consist in the directed formation of the microstructure of a cement matrix with accelerated formation of a hydrosilicate gel with a more homogeneous distribution of hydrates in a limited intergranular space and the formation of a homogeneous fine-crystalline structure of cement paste, are studied. On the basis of the analysis of the research results nanomodified ultrarapid hardening cementitious systems were developed based on the nanostructure formation types «top–down» and «bottom–up». Nanomodified ultrarapid hardening cementitious «top-down» systems are characterized by a significant increase in early strength after 1 and 2 days Rc1/Rc28=56.2 %; Rc2/Rc28=63.5 % respectively and standard strength (Rc28 = 60.8–66.9 MPa). According to these indicators they relate to ultrarapid and high strength binders. The ultrarapid hardening high strength cementitious systems obtained by bottom-up nanotechnology by introducing of suspension of synthesized calcium hydrosilicate nanosized particles, which are the centres of crystallization of C-S-H phases in the intergranular space, and polycarboxylate superplasticizers, are characterized by high rates of development of early strength of cement in high flowability conditions Rc1/Rc28 = 54% and high standard strength Rc28 = 84.8 MPa. The thesis has developed a systematic approach to the creation of effective High Performance concrete of a multi-level structure based on nanomodified ultrarapid hardening cementitious systems of «bottom-up» and «top-down» technologies. The scientific basis of the development of High Performance concrete with high technical and building properties, including impact resistance are designed. They are consisted in reducing the defect of the structure of the surface layer and the transition zone, the growth of the solid phase during the optimization of the system by introducing elements of various scale levels, as well as the formation of an increased number of hydrated products in matrix, dispersion reinforcement of the structure. Designed High Performance concretes are characterized by improved technological, strength and operational properties - consistence classes of fresh concrete S4–S5, rapid strength development (fcm2/fcm28 = 0.56–0.72), high-strength (class C55/67), water absorption 1.9–2.1%, increased water resistance (W18–W20), frost resistance (F300–F400). The modulus of elasticity of nanomodified concrete is 41.2–53.6 GPa, the Poisson's ratio is reduced to 0.17. Designed nanomodified self-compacting, fiber-reinforced self-compacting concrete mixtures meet the requirements for flow class SF3 and are characterized by homogeneity and resistance to sedimentation, and concrete on their basis characterized a rapid strength development under normal hardening conditions (fcm2/fcm28 = 0.55–0.62). Compressive strength classes of fiber-reinforced concretes based on nanomodified ultrarapid hardening cementitious systems are C 50/60-C60/75, the critical stress intensity factor increases in 1.2 times and the impact strength in 11.5 times compared to unreinforced concrete. High Performance concrete on the basis of nanomodified ultrarapid hardening cementitious systems at the expense of increasing the density of cement paste, accelerating the process of hydration and pozzolanic reaction are characterized by high early and standard strength; under the elevated temperatures up to 400 C their strength further increases by 20–30%. Тhe results of industrial approbation of the developed nanomodified ultrarapid hardening cementitious systems and concretes on their base are presented in the concreting of bearing monolithic structures, and the technical and economic efficiency of their application are shown. Тhe оbtained theoretical and methodological developments concerning the design of High Performance concrete on the basis of nanomodified ultrarapid hardening cementitious system are used in the educational process.
Наномодифицированные сверхбыстротвердеющие цементирующие системы и высокофункциональные бетоны на их основе
Nanomodified ultrarapid hardening cementitious systems and High Performance concrete on their base
Keywords: наномодифікування; надшвидкотверднучі цементуючі системи; високофункціональні бетони багаторівневої структури; раннє структуроутворення; дисперсне армування; будівельно-технічні властивості; наномодифицирование; сверхбыстротвердеющие цементирующие системы; высокофункциональные бетоны многоуровневой структуры; раннее структурообразование; дисперсное армирование; строительно-технические свойства; nanomodification; ultrarapid hardening cementitious systems; High performance concretes of multi-level structure; multilevel reinforcing; building and technical properties; 666.942.32:666.9.035